EMPLOYEE OUTPUT OF SELECTED DEPOSIT MONEY BANKS IN OGUN STATE, NIGERIA: THE ROLE OF WORKPLACE HEALTH AND SAFETY - Edafe Bawa DOGO; Mercy Ijeuru FRANCIS-ODII; Oluwajuwon Gabriel ARIYO; Mercy Olohigbe FELIX-NWAKALAMBA (Malete Journal of Accounting and Finance, 2025)
Employee output is a critical concern for both managers and academics. Despite various efforts to enhance output levels in deposit money banks in Nigeria, issues such as declining productivity, performance inefficiencies, increased absenteeism, and service variability continue to undermine employee output. While workplace health and safety has been studied in literature as it relates to various employee performance metrics, its specific impact on employee output, particularly in deposit money banks in Ogun State, Nigeria, remains underexplored. This study, therefore, examined the effect of workplace health and safety on employee output in selected deposit money banks in Ogun State, Nigeria. A survey research design was employed, following a quantitative and deductive approach. A total of 403 employees were sampled from three selected deposit money banks in Ogun State, Nigeria. Primary data were collected using a structured and validated questionnaire and analyzed using inferential statistics (regression analysis) at a 5% significance level. The findings revealed a statistically significant positive effect of workplace health and safety on employee output (β = 0.086, t = 3.217, p < 0.05) in the selected banks. The study concluded that deliberate investment in workplace health and safety enhances employee performance and serves as a strategic tool for boosting employee output. It is recommended that managers empower health, safety, and human resource departments through dedicated budgets, training programs, and clearly defined authority to routinely review, update, and enforce comprehensive workplace health and safety policies. Enhanced workplace health and safety leads to sustained employee output and supports long-term institutional growth.